2014
DOI: 10.1088/0957-0233/25/9/095203
|View full text |Cite
|
Sign up to set email alerts
|

Two-wavelength Raman imaging for non-intrusive monitoring of transient temperature in microfluidic devices

Abstract: The present study proposes a non-intrusive visualization technique based on two-wavelength Raman imaging for in-situ monitoring of the unsteady temperature field in microfluidic systems. The measurement principle relies on the contrasting temperature dependencies of hydrogen-bonded and non-hydrogen-bonded OH stretching modes of the water Raman band, whose intensities were simultaneously captured by two cameras equipped with corresponding bandpass filters. The temperature distributions were then determined from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…The typical value for the standard deviation was 0.120 at 296 K, which corresponds to 9.1 K in temperature according to the slope of the calibration curve (−0.0133 K -1 ). In our previous study (Kuriyama and Sato, 2014), the calibration result showed a linear relationship between Raman intensity and temperature in a similar way, whereas the typical standard deviation of the intensity ratio was relatively small (equivalent to 1.5 K) compared to the present study due to the long exposure time (500 ms) and temporal averaging process over 30 successive Raman images. This result indicates that the variation in intensity ratio leads to a considerably large temperature error within the measurement area especially when the fast image acquisition is required.…”
Section: Results and Discussion 41 Calibration Experimentssupporting
confidence: 79%
See 1 more Smart Citation
“…The typical value for the standard deviation was 0.120 at 296 K, which corresponds to 9.1 K in temperature according to the slope of the calibration curve (−0.0133 K -1 ). In our previous study (Kuriyama and Sato, 2014), the calibration result showed a linear relationship between Raman intensity and temperature in a similar way, whereas the typical standard deviation of the intensity ratio was relatively small (equivalent to 1.5 K) compared to the present study due to the long exposure time (500 ms) and temporal averaging process over 30 successive Raman images. This result indicates that the variation in intensity ratio leads to a considerably large temperature error within the measurement area especially when the fast image acquisition is required.…”
Section: Results and Discussion 41 Calibration Experimentssupporting
confidence: 79%
“…This is similar in concept to Takahashi's methodology but it measures temperature (instead of concentration) for velocity determination. We assume that a pulsed heating is given in an upstream region of a channel flow and that the time-series temperature is probed in the downstream area using two-wavelength Raman imaging, which was proposed for non-intrusive temperature visualization (Kuriyama and Sato, 2014). If the temperature rise by the pulsed heating is successfully detected by Raman imaging, fluid velocity (v) can be obtained from the displacement of the peak temperature (∆x) and the time interval (∆t), i.e., v = ∆x/∆t.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose a label‐free method for evaluating and visualizing both intracellular and extracellular temperatures simultaneously using the Raman imaging of water inside a cell. Raman microscopy is one of the most powerful methods for observing living systems, and we pay attention to the fact the shape of the O−H stretching Raman band of water changes in accordance with temperature . We expected that a calibration curve obtained from the shape of the O−H stretching band and the temperature at each intracellular or extracellular region would enable temperature measurements of various regions.…”
Section: Figurementioning
confidence: 99%
“…In this study, we propose a label‐free method for evaluating and visualizing both intracellular and extracellular temperatures simultaneously using the Raman imaging of water inside a cell. Raman microscopy is one of the most powerful methods for observing living systems, and we pay attention to the fact the shape of the O−H stretching Raman band of water changes in accordance with temperature . We expected that a calibration curve obtained from the shape of the O−H stretching band and the temperature at each intracellular or extracellular region would enable temperature measurements of various regions.…”
Section: Figurementioning
confidence: 99%